The Asymmetric Relation Between Initial Margin Requirements and Stock Market Volatility Across Bull and Bear Markets - Hardouvelis, Gikas A.; Theodossiou, Panayiotis (Review of Financial Studies, 2002)
Higher initial margin requirements are associated with lower subsequent stock market volatility during normal and bull periods, but show no relationship during bear periods. Higher margins are also negatively related to the conditional mean of stock returns, apparently because they reduce systemic risk. We conclude that a prudential rule for setting margins (or other regulatory restrictions) is to lower them in sharply declining markets in order to enhance liquidity and avoid a depyramiding effect in stock prices, but subsequently raise them and keep them at the higher level in order to prevent a future pyramiding effect